UPAYA MENINGKATKAN PEMAHAMAN UMAT TENTANG EKARISTI MELALUI KATEKESE DI STASI SANTA MARIA ASSUMPTA RUNGUN PAROKI AVE MARIA TANJUNG - Deriana Kasan; Romanus Romas; Paulina Maria. E.W; Greget Widhiati (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2021)
This study aims to determine the people‟s understanding of the Eucharist, the involvement of the people in the celebration of the Eucharist and to incerease the people‟s understanding of the Eucharist through catechesis at the Santa Maria Assupta Rungun Parish Ave Maria Tanjung Station. Through catechesis, people are expected to understand the Eucharist as the source and peak of Christian life. This type of research is descriptive qualitative. Data obtained by using interviews and documentation. The research was conducted in May at the Santa Maria Asumta Rungun station. There were 10 informants in this study consisting of 1 parish priest, head of the congregation and 8 people. The data analysis technique uses Miles and Huberman which consists of 3 stages, namely reduction, data presentation, and drawing conclusions.